Pengaruh marketing mix terhadap minat memiliki tabungan easy wadiah pada Bank Syariah Indonesia - Fifi Nur Haryanti; Shekar Maulida Salsabila; Mufti Arief Arfiansyah (Fakultas Ekonomi dan Bisnis Islam UIN Raden Mas Said Surakarta, 2023)
Indonesia is a country with a majority Muslim population. Where many Indonesian people should manage their finances through Islamic banks. However, in reality, the market share of Islamic banks is still small compared to conventional banks. It is necessary to do research on the interest of the Indonesian people to have Islamic bank products. This study aims to analyze the influence of the marketing mix on the intention to have easy wadiah savings at Bank Syariah Indonesia. This study uses a data processing tool in the form of SPSS. This type of research is quantitative primary data with simple random probability techniques and data collection using a questionnaire of 142 respondents. The research variable uses the 4P marketing mix theory. Based on the test results, it shows that product, price, and promotion variables affect the interest in having easy wadiah savings at BSI. Meanwhile, the location variable does not affect interest in having easy wadiah savings at BSI